2004
DOI: 10.1111/j.1545-5300.2004.00032.x
|View full text |Cite
|
Sign up to set email alerts
|

The Formation of the Therapeutic Alliance in Couple Therapy

Abstract: This study examines the predictive validity of several clinical variables--including marital distress, individual symptomatology, and family-of-origin experiences--on the formation of the alliance in couple therapy. Eighty people who were treated with a naturalistic course of integrative conjoint psychotherapy at a large midwestern outpatient clinic were assessed on the clinical variables before session 1. They also completed ratings of the therapeutic alliance after sessions 1 and 8. Individual symptomatology… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
88
1
6

Year Published

2011
2011
2015
2015

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(98 citation statements)
references
References 40 publications
3
88
1
6
Order By: Relevance
“…Specifically, it was found that when male symptom distress was high, the alliance was low. This finding is of particular interest as virtually all of the published literature states that individual symptom distress has no bearing on the alliance in couple therapy (Knobloch-Fedders et al, 2004;Mamodhoussen et al, 2005). It illustrates the necessity of further study of the alliance in couple therapy.…”
Section: Discussionmentioning
confidence: 78%
“…Specifically, it was found that when male symptom distress was high, the alliance was low. This finding is of particular interest as virtually all of the published literature states that individual symptom distress has no bearing on the alliance in couple therapy (Knobloch-Fedders et al, 2004;Mamodhoussen et al, 2005). It illustrates the necessity of further study of the alliance in couple therapy.…”
Section: Discussionmentioning
confidence: 78%
“…The categories and processes which were distinguished can be referred to research studies associating drop-out with a failure to conceptualize the problem [33,34] and a failure to define mutual expectations about the method of solving this problem [13,35,36] as well as to studies which emphasize the importance of establishing a therapeutic alliance with at least two persons [28]. It should also be underlined that split alliances mostly appear at the beginning of therapeutic processes [21].…”
Section: Discussionmentioning
confidence: 99%
“…The identified categories of 'split working alliance' and 'split therapeutic bond' refer to the notion of "split alliance" which is present in the literature [18][19][20][21]. This applies to significant differences in the perception of the therapeutic process by its individual participants.…”
Section: : My Intervention Was Too Early Perhaps If It Had Happened mentioning
confidence: 99%
“…The relationship I have as a postmodern therapist with my couples/families can determine what the outcome of our sessions will be (Knoblock-Fedders, Pinsof, & Mann, 2004). Bordin (1979) went so far as to say that the "working alliance between the person who seeks change and the one who offers to Downloaded by [University of Toronto Libraries] at 12:20 20 December 2014 be a change agent is one of the keys, if not the key, to the change process" (p. 252).…”
Section: Therapeutic Alliancementioning
confidence: 99%